استراتيجيات ترجمة المصطلحات الثقافية في قصة الكاريكاتير الملايوية ‹ Budak Kampungإلى اللغة العربية ؛ دراسة وصفية تحليلية › - نور أزرين بنت زينل
Each country has a different culture where, for example, in the same state and district, the language and dialect used are different and they determine their own culture. This shows that the language transition that occurs in translation activities is closely related to an inseparable culture. Therefore, this study attempts to identify how a translator deals with cultural words in the source text in the Budak Kampung comic, by Dato’ Lat, to be translated into the Arabic Language. This study also examines the cultural category found in the Budak Kampung comic according to the theories of Peter Newmark (1988) and the strategies used by the translator in translating those cultural words based on the theory of Newmark (1988). The researcher used a qualitative descriptive method using content analysis technique to study the text. The study found that translator employed several strategies from translation theory that have been pointed out in this study in translating Budak Kampung comics into Arabic such as cultural equivalence, functional equivalence and borrowing.